2006
DOI: 10.1152/ajpendo.00287.2005
|View full text |Cite
|
Sign up to set email alerts
|

In vivo rates of erythrocyte glutathione synthesis in adults with sickle cell disease

Abstract: Reid, Marvin, Asha Badaloo, Terrence Forrester, and Farook Jahoor. In vivo rates of erythrocyte glutathione synthesis in adults with sickle cell disease. Am J Physiol Endocrinol Metab 291: E73-E79, 2006. First published January 24, 2006 doi:10.1152/ajpendo.00287.2005.-Despite reports of lower GSH concentration in sickle cell disease (SCD), the in vivo kinetic mechanism(s) responsible for GSH deficiency is unknown. To determine whether suppressed synthesis was responsible for the lower erythrocyte GSH concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 42 publications
5
55
0
1
Order By: Relevance
“…Our findings are consistent with other studies suggesting that lower erythrocyte GSH in SCD patients is not reflective of reduced substrate availability or decreased synthesis, but rather increased GSH consumption. 13,75 Glutathione depletion has long been known to occur in the plasma and erythrocytes of SCD patients. 14,15,17,18,32,75 By evaluating Figure 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with other studies suggesting that lower erythrocyte GSH in SCD patients is not reflective of reduced substrate availability or decreased synthesis, but rather increased GSH consumption. 13,75 Glutathione depletion has long been known to occur in the plasma and erythrocytes of SCD patients. 14,15,17,18,32,75 By evaluating Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular GSH concentrations are significantly reduced in response to protein malnutrition, oxidative stress, aging, and many pathologic conditions, 1,10 including sickle cell disease (SCD), 13-18 a hemoglobinopathy associated with vasoocclusive and hemolytic complications. [19][20][21][22][23][24][25][26] Sickle erythrocytes have a shortened survival time and are more susceptible to oxidant damage than red blood cells from healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…This process can contribute to vascular dysfunction, hemolysis, and a pro-thrombotic state. 32 Finally, alterations in the glutathione buffering system common to these hemoglobinopathies 30,33 may render erythrocytes incapable of handling the increased oxidant burden, thereby predisposing them to hemolysis. Recently we discovered that a depletion of erythrocyte glutamine concentration and aberrations in erythrocyte glutathione metabolism is linked to severity of PH in SCD and biomarkers of hemolytic rate.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…As expected, our experiments detected greater hemoglobin oxidation and lipid peroxidation in the erythrocytes of SS patients. A majority of studies on the SCD population have reported deficits in concentration of GSH (Hebbel et al, 1982;Wetterstroem, 1984;Hebbel, 1990;Hebbel, Leung, Mohandas, 1990;Aslan, Thornley-Brown, Freeman, 2000;Reid et al, 2006;Morris et al, 2008), while others have not found this pattern (Rice-Evans, Omorphos, Baysal, 1986;Somjee et al, 2004;Manfredini et al, 2008;Nur et al, 2011). Moreover, the GSSG (oxidized glutathione)/ GSH index was significantly elevated in SCD patients, supporting an important role for oxidative damage in these cells (Morris et al, 2008;Rusanova, 2010).…”
Section: Discussionmentioning
confidence: 99%